Mollusc Community Structure in Deep Ambon Bay Waters - Pesilette, Rosmi; Natan, yuliana; Uneputti, Pruley Annete (Masyarakat Moluska Indonesia, 2025)
Inner Ambon Bay has quite abundant fishery resources. Mollusks are one of the aquatic resources in Inner Ambon Bay, and have been used by the community for a long time. Environmental damage due to settlement expansion, sand mining, resort and café construction as well as over-harvesting of biota have an impact on the sustainability of mollusks in the waters of Inner Ambon Bay. This study aims to analyze the community structure of mollusks which include density, abundance, diversity, diversity and dominance as well as distribution patterns. This research was conducted in January 2024, using the square transect method at three research locations. Namely Tanjung Tiram, Poka Village, Waiheru Beach and Passo Beach. The mollusks obtained were 36 species consisting of 22 species of the gastropod class and 14 species of the bivalve class. The most widely found mollusks are mollusks of the class of gastropods of the family Nassaridae species Hebra corticata, and species that the least found were from the Genus Bursa, Cymatium and Nerita, the value of the diversity index (H') = 2.166, the diversity index (E) = 0.604 and the dominance index (D) = 0.236. Patterns of dispersal of mollusks are random and in groups.